The relationship between biogenetic attributions and desire for social distance from persons with schizophrenia and major depression revisited. (August 2015) - Angermeyer, M. C.; Daubmann, A.; Wegscheider, K.; Mnich, E.; Schomerus, G.; Knesebeck, O. v. d.
<x content-type="archive" xml:space="preserve">Abstract</x> Aims. Previous population-based studies did not support the view that biological and genetic causal models help increase social acceptance of people with mental illness. However, practically all these studies used un-labelled vignettes depicting symptoms of the disorders of interest. Thus, in these studies the public's reactions to pathological behaviour had been assessed rather than reactions to psychiatric disorders that had explicitly been labelled as such. The question arises as to whether results would have been similar if respondents had been confronted with vignettes with explicit mention of the respective diagnosis. Methods. Analyses are based on data of a telephone survey in two German metropolises conducted in 2011. Case-vignettes with typical symptoms suggestive of depression or schizophrenia were presented to the respondents. After presentation of the vignette respondents were informed about the diagnosis. Results. We found a statistically significant association of the endorsement of brain disease as a cause with greater desire for social distance from persons with schizophrenia. In major depression, this relation was absent. With both disorders, there was no statistically significant association between the endorsement of hereditary factors as a cause and social distance. Conclusions. Irrespective of whether unlabelled or labelled vignettes are employed, the ascription to biological or genetic causes seems not to be associated with a reduction of the public's desire for social distance from people with schizophrenia or depression. Our results corroborate the notion that promulgating biological and genetic causal models may not help decrease the stigma surrounding these illnesses.